Modified endaural approach for the treatment of condylar fractures: A review of 75 cases - S M Balaji (Wolters Kluwer Medknow Publications, 2016)
Background: There are several treatment approaches for mandibular condyle fractures. Type of fracture, clinical experience, and preference of the operating surgeon dictate the approach. Given this highly varied outcome, this manuscript intends to document the treatment experience of 75 patients with extracapsular condyle fractures using author's modification of the traditional endaural approach in the region. Materials and Methods: A retrospective chart review was performed on patients with mandibular condylar fractures who visited the author's center between 2004 and 2014. For the surgical reduction and fixation, an endaural (ear) approach via the author's modification of Al-Kayat Bramley's incision in the superficial temporal region was used. Postoperative clinical parameters were evaluated which include the degree of mouth opening, chin deviation during mouth opening, occlusal relationship, temporomandibular joint function, radiographic stability, and other postoperative complications of condylar fractures such as infection, plate fracture, and permanent paralysis of facial nerve. Adolescence/adult patients with unilateral/bilateral condylar fracture who underwent open reduction with the follow-up of at least 1 year were included in the study. Edentulous and patients <15 years who underwent closed treatment were excluded from the study. Results: The study group consisted of 75 cases of mandibular condyle fractures, of which 55 cases were of unilateral condyle fractures and 20 cases were of bilateral condylar fractures. Postoperative follow-up of patients ranged from 1 to 10 years with the mean of 3.04 ± 1.93 years. The occlusal relationships were excellent in all with the mean degree of mouth opening of 40.11 mm (maximum 4.5 cm and minimum 2.9 cm), of which four patients reported restricted mouth opening. Orthopantomogram and computed tomography showed complete anatomical reduction of the condyle fracture in all patients. Nine out of 75 patients developed transient facial weakness, with no other postoperative complications of condylar fractures such as infections, plate fracture, and permanent paralysis of facial nerve were noted. The overall success rate was 92%. Conclusion: Surgery for mandibular condyle fractures with modified approach allows direct vision of the fracture and reduces surgical trauma to the site while avoiding permanent facial nerve injury. Hence, the author's modified Al-Kayat Bramley incision via endaural approach could be considered as the best approach for open reduction and internal fixation of condylar neck and subcondylar mandibular fractures.